Professor Sergii Volodymyrovych Filatov: Just a son in the shadow of a great father or a prominent ophthalmologist? (Ukrainian Journal of Ophthalmology, 2025)
Professor Sergii Volodymyrovych Filatov: Just a son in the shadow of a great father or a prominent ophthalmologist?